2011
DOI: 10.1155/2011/185354
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Genes in Defining a Molecular Biology of PTSD

Abstract: Abstract. Because environmental exposure to trauma is the sine qua non for the development of Post Traumatic Stress Disorder (PTSD), the recent focus on genetic studies has been noteworthy. The main catalyst for such studies is the observation from epidemiological studies that not all trauma survivors develop this disorder. Furthermore, neuroendocrine findings suggest preexisting hormonal alterations that confer risk for PTSD. This paper presents the rationale for examining genetic factors in PTSD and trauma e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(36 citation statements)
references
References 71 publications
1
35
0
Order By: Relevance
“…Taken together, these data are consistent with evidence suggesting that genetic variability contributes to disparities in risk and severity of PTSD (Pitman et al, 2012;Yehuda et al, 2011), and in particular with the identification of APOE as one of these genetic markers (Freeman et al, 2005;Kim et al, 2013). In a group of chronic, combat-related PTSD subjects (n = 44), Freeman et al (2005) demonstrated an association between possession of E2 and more severe re-experiencing symptoms and poorer performance on several memory tests (1).…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Taken together, these data are consistent with evidence suggesting that genetic variability contributes to disparities in risk and severity of PTSD (Pitman et al, 2012;Yehuda et al, 2011), and in particular with the identification of APOE as one of these genetic markers (Freeman et al, 2005;Kim et al, 2013). In a group of chronic, combat-related PTSD subjects (n = 44), Freeman et al (2005) demonstrated an association between possession of E2 and more severe re-experiencing symptoms and poorer performance on several memory tests (1).…”
Section: Discussionsupporting
confidence: 84%
“…It has been estimated that close to 90% of people are exposed to at least one traumatic event, such as rape, assault, disaster, rescue work, or combat, over the course of their lifetime (Kilpatrick et al, 2013). However, PTSD develops only in a subgroup of people exposed to a traumatic event, with the lifetime prevalence of PTSD estimated between 7.8 and 8.7% (Kessler et al, 1995(Kessler et al, , 2005, thus supporting a role for genetic risk factors (Pittman et al, 2012;Yehuda et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…This procedure causes increased anxiety, impaired cognition, cardiovascular reactivity and startle response, as well as an exaggerated response to yohimbine similar to that of human PTSD patients [64] . The idea that epigenetic DNA modification plays a fundamental role in anxiety disorders such as PTSD has been around for a while, and long-term traumatic memory expression is considered to be important in this process [85] . The brain-derived neurotrophic factor gene has been found to be selectively methylated in the hippocampus of rats that underwent the PPS paradigm, which supports the theory that traumatic stress causes (epigenetic) changes in brain regions regulating cognition and stress regulation.…”
Section: Ppsmentioning
confidence: 99%
“…In fact, more than 30% of the variance for PTSD risk is attributed to genetic factors, as evidenced by family and twin-heritability studies (Lyons et al, 1993;Sack et al, 1995;Yehuda et al, 2001;Stein et al, 2002;Kremen et al, 2012). More than 30 candidate gene studies have been performed [for reviews see Cornelis et al (2010) and Yehuda et al (2011)]. These studies have produced inconsistent and sometimes contradictory results.…”
Section: Introductionmentioning
confidence: 99%